Short Term Outcome of High Dose Dexamethasone Versus Prednisone In Children With Acute Immune Thrombocytopenic Purpura: A Single Center Trial - Ahmed Osama Kaddah; Niveen Salama; Doaa Maged Ahmed; Mariam Saad Nassim (Pediatric Sciences Journal)
Background: Corticosteroids are the first line treatment of immune thrombocytopenia (ITP). While high dose dexamethasone (HD-DXM) can be used as a first line therapy in adults, data about its use in children is scarce. Aim of the work: To compare the efficacy of short-course HD-DXM and standard prednisone (PDN) as a first-line treatment to achieve increase in platelet count among children with previously untreated primary ITP. Materials and Methods: This prospective randomized controlled open label clinical trial was conducted on 60 children with newly diagnosed ITP randomized to either HD-DXM or PDN (30 patients in each group). HD-DXM was given at a dose of 24mg/m2/day (maximum dose 40mg/day) for 4 consecutive days and PDN was given at a dose 2mg/kg/day (maximum dose 60mg/day) for 7 consecutive days. Complete blood count was done at days 0,2,4,7,14,30 and 60. Results: The mean age in HD-DXM and PDN groups were 6 ± 2.9 years and 6 ± 3.5 years respectively (p=0.89). Females and males were 16 (53.3%) and 14 (46.7%) in HD-DXM and 13 (43.3%) and 17 (56.7%) PDN groups (p=0.795). The main symptom was epistaxis in 30(50%) of cases, followed by purpura in 18(30%), gum bleeding in 10(16.6%), and subconjunctival hemorrhage in 2(3.4%). Initial mean platelet count in HD-DXM and PDN was 5.4± 2.9 x 103 μl and 5.2 ± 4.2 x103 μl (p=0.444). Platelet count was 66.9±42.2 x103 μl and 37.3±61.5 x103 μl in HD-DXM and PDN groups at day 2 (p=0.002), 176.6±134 x103 μl and 108.6±135.8 x103 μl at day 4 (p=0.011), 132±134.7 x103 μl and 173.8±101.5 x103 μl at day 7 (p=0.016). There was no significant difference between the 2 groups in platelet counts at day 14 , 30, 60 (p=0.271), (p=0.982) and (p=0.706) respectively. Conclusion: HD-DXM achieved an earlier but unsustained rise of platelet count in newly diagnosed ITP than PDN. However, both medicines yielded the same effect during follow up period of two months.